Unani Perspectives on Migraine (Shaqīqa): Classical Insights and Clinical Applications - Alam, Md. Tauhid; Alam, Md. Tanwir; Akhtar, Jamal; Anjum, Sultana (Journal of Neonatal Surgery, 2025)
Migraine, known as Shaqīqa in Unani medicine, is a chronic neurological condition characterized by recurrent, unilateral headaches often accompanied by nausea, vomiting, photophobia, and phonophobia. Despite advancements in modern medicine, a significant number of migraine sufferers experience inadequate relief, prompting interest in complementary systems like Unani medicine, this provides a holistic approach to disease management. In Unani literature, Shaqīqa is recognized as a disorder of the brain (Amraz-e-Dimagh), resulting from humoral imbalance—particularly involving Safra (yellow bile), Sauda (black bile), and Dam (blood). Classical Unani scholars such as Ibn Sina, Al-Razi, and Ibn Rushd described Shaqīqa as a manifestation of disordered temperament (Mizaj) and the upward movement of noxious vapors (bukharat) from the stomach or liver to the brain. The condition is classified based on the dominant humor involved, aiding in personalized treatment. Unani management encompasses a triad of approaches: Ilaj bil Tadbeer (regimental therapy), including venesection, cupping, and massage; Ilaj bil Ghiza (dietotherapy), which emphasizes temperamental and seasonal dietary adjustments; and Ilaj bil Dawa (pharmacotherapy), involving time-tested herbal and compound formulations. This review integrates classical insights with contemporary evidence, highlighting the scientific rationale of Unani interventions in migraine management. The individualized and preventive focus of Unani medicine offers promising avenues for integrative care. Further clinical research and standardization of Unani protocols could enhance their applicability in modern healthcare frameworks for migraine.